Saluran Distribusi Dan Margin Pemasaran Moke Maumere Di Kota Makassar - Yohanes Soi; Aylee Christine Alamsyah Sheyoputri; Faidah Azuz (Fakultas Pertanian Universitas Bosowa, 2025)
Due to its unique flavor characteristics and deeply held cultural values, moke as a traditional alcoholic beverage not only functions as a drink but also as a symbol of local identity overseas. This causes migrants from Maumere, East Nusa Tenggara who live in Makassar City to always consume Moke from their home place as a medium of bonding and identity. This causes migrants from Maumere, East Nusa Tenggara who live in Makassar City to always consume Moke from their home place as a means of bonding and identity. It is within this context that the study of Moke distribution and marketing finds its relevance. In order to maximize market potential, however, it is important for producers or distributors to understand and manage distribution channels effectively. This study aims to determine the distribution channel model and the amount of Maumere moke marketing margin in Makassar city using quantitative descriptive method. Respondents in this study were 10 moke traders from Maumere in Makassar city. The results showed that the distribution channel of moke maumere in Makassar city showed quite good effectiveness, although it was still faced with several obstacles. A profitable marketing margin of Rp.30,000 / 600ml bottle shows great potential for business development. Karateristik rasa yang unik dan nilai budaya yang dipegang teguh, moke sebagai minuman tradisional beralkohol tidak hanya berfungsi sebagai minuman tetapi juga sebagai simbol identitas daerah (Maumere) di perantauan. Hal ini menyebabkan perantau asal Maumere Nusa Tenggara Timur yang berdomisili di Kota Makassar selalu mengonsumsi Moke dari daerah asal mereka sebagai alat perekat dan identitas. Dalam konteks inilah studi tentang distribusi dan pemasaran Moke menemukan relevansinya. Namun untuk memaksimalkan potensi pasar, penting bagi produsen atau distributor untuk memahami dan mengelola saluran distribusi secara efektif. Penelitian ini bertujuan untuk mengetahui model saluran distribusi dan besarnya margin pemasaran moke maumere di kota Makassar dengan menggunakan metode diskriptif kuantitatif. Informan dalam penelitian ini adalah pedagang moke asal Maumere di kota Makassar yang berjumlah 10 orang. Hasil penelitian menunjukkan bahwa saluran distribusi moke maumere di kota Makassar menunjukan efektivitas yang cukup baik, meskipun masih dihadapkan pada beberapa kendala. Margin pemasaran yang menguntungkan yaitu sebesar Rp.30.000/ botol kemasan 600ml menunjukkan potensi besar bagi pengembangan usaha.